Elevated Levels of sE-selectin in Post-menopausal Females Are Decreased by Hormone Replacement Therapy to Levels Observed in Pre-menopausal Females - Kennedy, Gwen; McLaren, Margaret; Belch, Jill J. F.; Seed, Mary (Thrombosis and Haemostasis, 1999)
Observational epidemological studies have shown that mortality from coronary heart disease is reduced in post-menopausal women by hormone replacement therapy (HRT). The aim of this study was to measure sE-selectin levels in post-menopausal females before and after HRT and to compare these with pre-menopausal females and aged matched males. Post-menopausal females (n = 70) were given HRT or no treatment to act as a control group. sE-selectin levels were significantly lower in the pre-menopausal (n = 36) when compared with the post-menopausal females (n = 70) (p = 0.027), whereas no difference between two age matched male groups was found (n = 40). Oral and transdermal HRT significantly decreased sE-selectin levels (p <0.0001 and p = 0.0005 respectively) with no change in the control group. The reduction in the levels of this marker of endothelial activation after HRT, may reflect a decrease in leucocyte/endothelial interaction which may reduce atherosclerotic risk in post-menopausal females.
Keywords: E-selectin; atherosclerosis; hormone replacement therapy; endothelium; leucocyte